Accuracy and Synchronization of Hadith: A Study of Al-Akhlāq Lilbanāt by Sheikh ‘Umar Ahmad Baraja’ - Yasti, Suci Amalia; Taufiqurrahman; Fithri, Widia (JOURNAL OF QUR'AN AND HADITH STUDIES, 2025)
This study examines Al-Akhlāq Lilbanāt by Sheikh ‘Umar bin Ahmad Baraja’, a key reference in the moral education curriculum of many Islamic boarding schools in Indonesia. The main problem identified is the use of hadiths presented only in matan form without clear references to primary hadith sources, raising questions about their authenticity and methodological accuracy. The research aims to evaluate the validity of these hadiths through analysis of citation, writing accuracy, and consistency of meaning compared to reputable hadith compilations. Using a comparative thematic analysis, the study finds that Sheikh ‘Umar prioritizes pedagogical and moral dimensions over strict methodological precision in transmission. Although references are often missing, the meanings of the hadiths remain consistent with authoritative sources. The findings suggest that the book’s educational impact is strengthened by its contextual relevance, yet it would benefit from annotated editions that include verified hadith sources to enhance scholarly reliability.